In Vitro and In Vivo Biology of Recombinant Adenovirus Vectors with E1, E1/E2A, or E1/E4 Deleted - Lusky, M. (American Society for Microbiology, 1998)
Isogenic, E3-deleted adenovirus vectors defective in E1, E1 and E2A, or E1 and E4 were generated in complementation cell lines expressing E1, E1 and E2A, or E1 and E4 and characterized in vitro and in vivo. In the absence of complementation, deletion of both E1 and E2A completely abolished expression of early and late viral genes, while deletion of E1 and E4 impaired expression of viral genes, although at a lower level than the E1/E2A deletion. The in vivo persistence of these three types of vectors was monitored in selected strains of mice with viral genomes devoid of transgenes to exclude any interference by immunogenic transgene-encoded products. Our studies showed no significant differences among the vectors in the short-term maintenance and long-term (4-month) persistence of viral DNA in liver and lung cells of immunocompetent and immunodeficient mice. Furthermore, all vectors induced similar antibody responses and comparable levels of adenovirus-specific cytotoxic T lymphocytes. These results suggest that in the absence of transgenes, the progressive deletion of the adenovirus genome does not extend the in vivo persistence of the transduced cells and does not reduce the antivirus immune response. In addition, our data confirm that, in the absence of transgene expression, mouse cellular immunity to viral antigens plays a minor role in the progressive elimination of the virus genome.